2018
DOI: 10.1371/journal.pone.0190781
|View full text |Cite
|
Sign up to set email alerts
|

How Japanese companion dog and cat owners’ degree of attachment relates to the attribution of emotions to their animals

Abstract: Recently, studies in the United States and European countries have shown that the degree of attachment is associated with the attribution of emotions to companion animals. These studies imply that investigating the degree of attachment to companion animals is a good way for researchers to explore animal emotions and then improve animal welfare. Although a promising area of study, in Japan, no empirical studies have examined the correlation between the degree of attachment and the attribution of emotions to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
3
24
0
1
Order By: Relevance
“…These emotion terms may be more efficient at communicating with pet owners because they resonate among the owners. A resemblance of the terms between pet owners and pets was found in this study, which could be a result of anthropomorphism as discussed in other studies (Arahori et al, 2017;Konok et al, 2015;Martens et al, 2016;Morris et al, 2008;Su et al, 2018). Pet owners were able to read signs/body languages of their cats and dogs related to positive/negative emotions, in which the interpretation was consistent with previous studies (Crowell-Davis, 2007;Tami & Gallagher, 2009;Turner, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…These emotion terms may be more efficient at communicating with pet owners because they resonate among the owners. A resemblance of the terms between pet owners and pets was found in this study, which could be a result of anthropomorphism as discussed in other studies (Arahori et al, 2017;Konok et al, 2015;Martens et al, 2016;Morris et al, 2008;Su et al, 2018). Pet owners were able to read signs/body languages of their cats and dogs related to positive/negative emotions, in which the interpretation was consistent with previous studies (Crowell-Davis, 2007;Tami & Gallagher, 2009;Turner, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Singh [37] provides evidence that the nuclear family has arrived as the dominant form of familial residence, particularly in urban centers where education and occupational specialization thrive. If the SDT in India follows trends seen in other cultures [7,8,11,13,18,19,20], the attitudes our respondents displayed toward pet dogs may suggest that upcoming generations may preference pets and personal authenticity over familial expectations of marriage and large families, at least in the higher socioeconomic groups.…”
Section: Discussionmentioning
confidence: 86%
“…Based upon our observations of where, and when, pet keeping and pet parenting practices develop, the SDT serves as a catalyst to move pet dogs into the higher affect , moderate utility quadrant of Serpell’s model. South Korea [18], Japan [19], and China [20] are each showing signs of embracing pet dogs in this way.…”
Section: Introductionmentioning
confidence: 99%
“…The findings did, however, indicate that the pupillary contagion response does occur to animal images and in particular, animals that are the most common type of pets. Pets are important to many people, and research into the relationships between people and their pets can provide a greater understanding of the complexities underlying these relationships and it might contribute to the understanding of people’s perception and treatment of animals ( Alba and Haslam, 2015 ; Su et al , 2018 ). A recent study has revealed that people are sensitive to cats’ affective states from subtle facial cues ( Dawson et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%